CRLF1–MYH9 Interaction Regulates Proliferation and Metastasis of Papillary Thyroid Carcinoma Through the ERK/ETV4 Axis - Yu, Shi-Tong; Sun, Bai-Hui; Ge, Jun-Na; Shi, Jiao-Long; Zhu, Man-Sheng; Wei, Zhi-Gang; Li, Ting-Ting; Zhang, Zhi-Cheng; Chen, Wei-Sheng; Lei, Shang-Tong (Frontiers in Endocrinology, 2020)
n our previous study, we have shown that CRLF1 can promote proliferation and metastasis of papillary thyroid carcinoma (PTC), however, the mechanism is unclear. Herein, we investigated whether the interaction of CRLF1 and MYH9 regulates proliferation and metastasis of PTC cells via ERK/ETV4 axis. Immunohistochemistry (IHC), qPCR, and western blotting assays were performed on PTC cells and normal thyroid cells to profile specific target genes. In vitro assays and in vivo assays were also conducted to examine the molecular mechanism. Results showed that CRLF1 directly bound MYH9 to enhance the stability of CRLF1 protein. Inhibition of MYH9 in PTC cells overexpressing CRLF1 significantly reversed malignant phenotypes, and CRLF1 overexpression activated ERK pathway, in vitro, and in vivo. RNA-sequencing revealed that ETV4 is a downstream target gene of CRLF1 which was up-regulated following ERK activation. Moreover, revealed that ETV4 is highly expressed in PTC tissues and is associated with poor prognosis. Finally, the ChIP assays showed that ETV4 induces the expression of matrix metalloproteinase 1(MMP1) by binding to its promoter on PTC cells. Altogether, our study demonstrates that CRLF1 interacts with MYH9, promoting cell proliferation and metastasis via ERK/ETV4 axis in PTC.